Kuṟiñcippāṭṭu patippu varalāṟu, 1889 - 2011 - Nittiyā Ar̲avēntan̲ (Kāvyā, 2013)
History of publishing of Kurincippattu, little literature, from 1889-2011
Tamil in Tamil-Schr
Keywords: Sangamliteratur; Liebeslyrik; Edition; Geschichte 1889-2011